2016
DOI: 10.1002/macp.201600113
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Electric Field Exposed P3HT Thin Films Using Polarized‐Light Spectroscopies

Abstract: P3HT (poly (3‐hexylthiophene)) has been widely used as a donor in the active layer in organic photovoltaic devices. Although moderately high‐power conversion efficiencies have been achieved with P3HT‐based devices, structural details, such as the orientation of polymer units and the extent of H‐ and J‐aggregation are not yet fully understood; and different measures have been taken to control the ordering in the material. One such measure, which has been exploited, is to apply an electric field from a Van de Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
(125 reference statements)
1
2
0
Order By: Relevance
“…Again, linecuts shown in Figure S2b of the (100) peak display reduced fwhm of 20.1 ± 0.16° for films exposed to vertical E-field compared to the control (25.8 ± 0.19°), horizontal (26 ± 0.24°) and tilted (25.7 ± 0.83°) cases. Our published work on fluorescence and Raman measurements affirms our GIWAXS results that the static forces of E-field induce anisotropic orientation in P3HT-only thin films. So far, we showed that E-field plays critical role in tailoring the surface morphology and phase distribution in P3HT-PCBM BHJ.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Again, linecuts shown in Figure S2b of the (100) peak display reduced fwhm of 20.1 ± 0.16° for films exposed to vertical E-field compared to the control (25.8 ± 0.19°), horizontal (26 ± 0.24°) and tilted (25.7 ± 0.83°) cases. Our published work on fluorescence and Raman measurements affirms our GIWAXS results that the static forces of E-field induce anisotropic orientation in P3HT-only thin films. So far, we showed that E-field plays critical role in tailoring the surface morphology and phase distribution in P3HT-PCBM BHJ.…”
Section: Resultssupporting
confidence: 88%
“…Again, linecuts shown in FigureS2bof the (100) peak display reduced fwhm of 20.1 ± 0.16°for films exposed to vertical E-field compared to the control (25.8 ± 0.19°), horizontal (26 ± 0.24°) and tilted (25.7 ± 0.83°) cases. Our published work on fluorescence and Raman measurements47…”
mentioning
confidence: 99%
“…These results are in agreement with the parameters of molecular ordering of the P3HT and P3OT LS films before and after gas exposure ( Table 2). Differences in the values of I C-C /I C=C and FWHM of C=C mode found for the LS film of P3HT before and after gas exposure confirm that the morphology of this film was more affected than the LS film of P3OT, resulting in higher molecular disorder [44] which represents a limitation to the carrier mobility in polymer matrices [45,46].…”
Section: Morphology Of P3ht and P3ot Ls Films Before And After Gas Exmentioning
confidence: 71%